PENERAPAN TEORI SOSIAL PADA PENELITIAN KUALITATIF AKUNTANSI - Cindy Vinella; Jason Wibisono; Maya Rianti; Maria Ellita Ovina; Carmel Meiden (Jurnal Ilmiah Hospitality, 2022)
The purpose of this research is to provide an overview related to the application of social theory in accounting practice. This research is carried out using the Systematic Literature Review (SLR) methodological approach. To search for journals related to research topics, researchers use search keywords: "social theory," "accounting information," and "accounting practices." This research raises important aspects in research such as the author's name, research title, journal name, year of research, number of research problems, number of theories, number of research steps, number of sites and informants, number of results and discussions, number of references, and unique things in each journal. This study was conducted on a sample of 40 published literature studies that were successfully collected during the research period from 2010-2022. The results showed that three theories are most often used in research with the theme of social theory, including phenomenological theory (according to Edmund Husserl), structure theory (according to Anthony Giddens), and ethnomethodology theory (according to Garfinkel). This study provides information for the next researcher who will research social theory to be used as a reference in developing his research.